2006
DOI: 10.1002/bit.21104
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cryptosporidium parvum oocysts using a microfluidic device equipped with the SUS micromesh and FITC‐labeled antibody

Abstract: Development of a microfluidic device equipped with micromesh for detection of Cryptosporidium parvum oocyst was reported. A micromesh consisting of 10 x 10 cavities was microfabricated on the stainless steel plate by laser ablation. Each cavity size, approximately 2.7 microm in diameter, was adopted to capture a single C. parvum oocyst. Under negative pressure operation, suspensions containing microbeads or C. parvum oocysts flowed into the microchannel. Due to strong non-specific adsorption of microbeads onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
(22 reference statements)
1
32
0
Order By: Relevance
“…Some previously published reports from our lab and elsewhere A large number of fi eld applications showed that the O157 immunomagnetic method greatly improved the isolation rate of bacteria [Buesa et al, 2002;Wolf et al, 2007]. The clinical samples for diagnosis are initially treated with a specifi c antibody-coated beads, and the target bacteria after reaction with their specifi c antibody are separated from other bacteria by immunomagnetic separation (IMS) [Bapanpally et al, 2014;Taguchi et al, 2007]. Loop-mediated isothermal amplifi cation (LAMP) is a sensitive, specifi c, convenient and fast nucleic acid amplifi cation technology, which obviates the need for expensive thermal cyclers used in conventional PCR [Saito et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Some previously published reports from our lab and elsewhere A large number of fi eld applications showed that the O157 immunomagnetic method greatly improved the isolation rate of bacteria [Buesa et al, 2002;Wolf et al, 2007]. The clinical samples for diagnosis are initially treated with a specifi c antibody-coated beads, and the target bacteria after reaction with their specifi c antibody are separated from other bacteria by immunomagnetic separation (IMS) [Bapanpally et al, 2014;Taguchi et al, 2007]. Loop-mediated isothermal amplifi cation (LAMP) is a sensitive, specifi c, convenient and fast nucleic acid amplifi cation technology, which obviates the need for expensive thermal cyclers used in conventional PCR [Saito et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The LOD was reported as 36 oocysts mL −1 , above the desired ability to detect single oocysts. 69 In 2001 Stokes and coworkers developed a sandwich immunoassay in a 0.4 mL reaction chamber on-chip, demonstrating E. coli detection. In the same year McClain et al employed a microfluidic flow cytometry setup for E. coli detection.…”
Section: In Optical Methodsmentioning
confidence: 99%
“…69 The maximum flow rate tested was 350 µL min −1 , so 5 mL could be processed in under 15 min. When loading a 0.5 mL test sample (spiked oocysts in PBS) at a concentration of 36 oocysts mL −1 a recovery rate of 93% from the mesh was reported, comparable to that achieved by off-chip IMS.…”
Section: Particles Properties Involvedmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibody coated on the surface of the IMB could capture the target organism when they are close to IMB. So IMS is a rapid, specific, efficient and technically simple method that can be used for separation of target organism directly from non-target organism and other particles without any need for centrifugation or filtration [14][15][16].…”
Section: Introductionmentioning
confidence: 99%